Pragmatic power of pronoun 'we' in official documents providing reports (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article describes the contexts of use of the pronoun we in the reporting documents. The considered methods language of demagoguery possible in these contexts. It is revealed that the pronoun cannot be regarded as a means of manipulation, because it is «inclusive» we where 2nd semantic component always clearly defined.
Keywords: the pronoun we; official document; manipulation; language demagoguer